Truth-tellers' and liars' synchrony during attitude-inconsistent conversations - Dunbar, Norah E.; Fujiwara, Ken; Bernhold, Quinten S. (Frontiers in Communication, 2023)
The recently-proposed strategic synchrony hypothesis holds that deceivers (moreso than truth-tellers) use nonverbal synchrony as a way to maintain their credibility and the smooth flow of interactions. However, important questions remain as to how an interaction partner’s behavior and the topic of interaction qualify the strategic synchrony hypothesis. This study considered whether naïve participants (i.e., truth-tellers and deceivers) synchronize differently to high- and low-involvement partners (i.e., confederates) depending on whether the partners discuss climate change or tuition increases, two salient conversational topics for our participants. Deceivers who discussed climate change with a high-involvement partner were especially likely to subjectively perceive that both they themselves and their partner initiated synchrony during the discussion of climate change. However, objective automated analyses of bodily movement synchrony revealed a different set of findings: Dyads with a truth-teller demonstrated higher increases in synchrony than dyads with a deceiver when moving from a superficial discussion of what they liked about their university to a direct discussion of climate change. Results are discussed in terms of how they advance the strategic synchrony hypothesis.